Symptomatic vulvovaginal candidiasis and antifungal resistance in HIV-1 positive women at Mbarara city health centre IV - Nusifah Mbatudde; Pauline Petra Nalumaga; Joel Bazira; Taseera Kabanda (Scientific Reports)
Abstract Vulvovaginal candidiasis (VVC) represents a universal health hazard that contributes to significant morbidity in HIV-positive women. Antifungal resistance is a worldwide increasing health problem that reduces treatment options while increasing treatment costs. The purpose of this study was to determine the prevalence of VVC, identify associated risk factors, characterize the distribution of Candida species, and assess their antifungal susceptibility patterns among HIV-positive women attending Mbarara City Health Centre IV. A laboratory-based, cross-sectional study design was conducted on 146 high vaginal swabs collected from HIV- positive women aged 18 years and above attending routine HIV care that presented with signs and symptoms of vulvovaginal candidiasis. These were subjected to microscopy and culture on Sabouraud Dextrose Agar. Candida isolates were identified by gram stain, germ tube, CHROM agar™, and Analytical profile index (API® Candida) tests. Susceptibility to fluconazole, clotrimazole, voriconazole, amphotericin B, miconazole, and nystatin by the disc diffusion method on Mueller Hinton agar supplemented with 2%w/v glucose and 0.5 µg/ml methylene blue dye. Out of the 146 high vaginal swabs collected, 71(49%) were colonized with Candida species with 43(62%) being Candida albicans while 26 (37.6%) were non-Candida albicans. Candida species were susceptible to amphotericin B (68/71, 95.7%) and resistant to fluconazole and clotrimazole (33/71, 45%). Elevated blood glucose levels were significantly associated with vulvovaginal candidiasis (p = 0.018; odds ratio = 2.93). Candida albicans is the leading cause of VVC, with a higher prevalence than non-Candida albicans. It also demonstrates that amphotericin B and nystatin are the most effective antifungal medications. Furthermore, diabetes is associated with VVC compared to other studied factors. We recommend the use of nystatin for the management of vulvovaginal candidiasis among HIV adult women.